Relationship between Toothbrushing Skills and Dental Caries in Class III – V Students of SDN 3 Ngasinan Ponorogo in 2024 - Krisyasinta Riyanandia Dewi Pramesti; Ida Chairanna Mahirawatie; Siti Fitria Ulfah; Silvia Prasetyowati (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
Dental caries is still often experienced by many people, including children. Elementary school age children aged 6-12 years are classified as vulnerable to dental caries. The problem of this research is the high rate of dental caries in students in grades III to V at SDN 3 Ngasinan Ponorogo, where almost all students have dental caries. The aim of the research was to determine the relationship between tooth brushing skills and dental caries in students in grades III to V at SDN 3 Ngasinan Ponorogo. This type of research is analytical research with a cross sectional method, with a sample of 32 students in class III to V at SDN 3 Ngasinan Ponorogo. The data collection instruments used were observation sheets and stopwatches to measure students toothbrushing skills as well as examination sheets to identify dental caries. The analysis technique uses the chi-square test. The results of research on the toothbrushing skills of students in grades III to V at SDN 3 Ngasinan Ponorogo were included in the low-skill category at 68.8%. Dental caries for students in grades III to V at SDN 3 Ngasinan Ponorogo was in the high category at 43.8%. There is a significant relationship between tooth brushing skills and dental caries in students in grades III to V at SDN 3 Ngasinan Ponorogo. Conclusion : The level of tooth brushing skills, both in terms of how to brush teeth and the duration of time for brushing teeth, will influence the level of dental caries in students.